2019
DOI: 10.1002/pdi.2221
|View full text |Cite
|
Sign up to set email alerts
|

Structured diabetes education outcomes: looking beyond HbA1c. A systematic review

Abstract: Diabetes education aims to equip people with diabetes with positive self‐care behaviours and management strategies to improve glycaemic control. The preferred outcome measure of education effectiveness is often HbA1c reduction. However, the move towards person‐centred education has led to renewed calls to capture associated behavioural and psychosocial change. The aim of this study was to review indicators of diabetes education efficacy in light of the growing emphasis on person‐centric care. A systematic sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(243 reference statements)
0
7
0
Order By: Relevance
“…In the current analysis, empowerment score increased by 20%, indicating a greater degree of confidence in the participants' perceived ability to manage their own health. Other analyses of SDE have also seen improvements in empowerment-related outcomes, 9,16 supporting this finding. It is likely that increased feelings of empowerment are at least partly responsible for the observed improvements in a range of health markers, but, as noted in the limitations below, it is not possible to assess this directly within the current audit.…”
Section: Discussionmentioning
confidence: 59%
“…In the current analysis, empowerment score increased by 20%, indicating a greater degree of confidence in the participants' perceived ability to manage their own health. Other analyses of SDE have also seen improvements in empowerment-related outcomes, 9,16 supporting this finding. It is likely that increased feelings of empowerment are at least partly responsible for the observed improvements in a range of health markers, but, as noted in the limitations below, it is not possible to assess this directly within the current audit.…”
Section: Discussionmentioning
confidence: 59%
“…More specifically the review found that successful diabetes education relied on facilitating change in participant cognition and behaviours, with psychosocial and behavioural change central in successful interventions. The review also confirmed diabetes education was more effective when led by Health care professionals (HCPs), with peer input, delivered in a group setting (40).…”
Section: Preliminary Workmentioning
confidence: 78%
“…The COM-B system allowed for clear As noted in the Results, the newly developed ORBIT intervention will allow for delivery of the identified behavioural change techniques to people with diabetes prior to commencing injectable treatment. In line with the translation of the behavioural change techniques, best practice guidelines and clinical guidelines will be used to guide same (20,33,40). Responding to this, the intervention should be delivered in a group setting, led by a trained HCP (Diabetes Specialist Dietitian), with opportunity for peer discussion and support.…”
Section: Discussionmentioning
confidence: 99%
“…23 Similarly, significant positive changes in behavioral and psychosocial outcomes such as diabetes knowledge, understanding, and condition management have also been reported. 24 Concerning cost-effectiveness, strong evidence exists in favor of DSMES compared to usual care. 25 Research has demonstrated that diabetes education significantly contributes to the reduction of risk for development of diabetes-related complications.…”
Section: Impact On Behavior Change Knowledge Clinical Humanistic and ...mentioning
confidence: 99%